The surgical treatment of destructive pulmonary tuberculosis in patients with diabetes - D. B. Giller; E. M. Glotov; O. Sh. Kesaev; A. A. Glotov; J. G. Imagozhev; P. G. Gadzhieva; A. A. Dulentsova; V. V. Koroev (Инновационная медицина Кубани, 2020)
The purpose of the study was to improve quality of surgical treatable of destructive pulmonary tuberculosis in patients with diabetes.Materials and Methods. D.B. Giller and employees of the Department of Phthisiopulmonology and Thoracic Surgery of the First Moscow State Medical University M.I. Sechenov performed operations on 200 patients with diabetes due to tuberculosis. Group 1 was mustered from 78 patients from 2004 to 2009. Group 2 was mustered from 122 patients from 2011 to 2017.Results. An analysis of the results showed that after 31 operations, 27 (13.5%) patients from both groups developed 33 complications. The second group (6.6%) had fewer complications after surgery than the first group (24.4%) 3.7 times. The first group had more vulnerary and bronchopleural complications than the second group. 12 patients (15.4%) of the first group and 6 patients (4.9%) of the second group had bronchopleural complications (empyema, residual cavity, delayed expansion of the lung and intrapleural bleeding). 2 patients died in the hospital (30-day mortality was 0.66%) after 303 surgical intervention in both groups. 1 patient (0.9%) died after 106 surgical interventions in the first group. 1 patient (0.5%) died after 197 surgical interventions in the second group. The full effect was achieved in 75 (96.2%) patients in the first group and 114 (93.4%) in the second group. The survival value of patients of the second group was 100% after 1 year, 98% after 2 years, 98.8% after 3 years, 96.9% after 4 years, 95.2% after 5 years. The surgical treatable affected the occupational rehabilitation of patients from group 2. 61.5% of patients from group 2 became able to work after 1 year. 64.5% of patients from group 2 became able to work after 5 years.Conclusion. If doctors use our tactics in patients with destructive pulmonary tuberculosis and diabetes, the risk of complications after surgery will drop and reactivation of tuberculosis will not occur.